2007
DOI: 10.1590/s1413-81232007000100018
|View full text |Cite
|
Sign up to set email alerts
|

A review of nitrates in drinking water: maternal exposure and adverse reproductive and developmental outcomes

Abstract: In this review, we present an update on maternal exposure to nitrates in drinking water in relation to possible adverse reproductive and developmental effects, and discuss nitrates in drinking water in the United States. The current standard for nitrates in drinking water is based on retrospective studies and approximates a level that protects infants from methemoglobinemia, but no safety factor is built into the standard. The current standard applies only to public water systems. Animal studies have found adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 32 publications
1
74
0
6
Order By: Relevance
“…Nitrate is a serious problem worldwide, and recent research indicated that nitrate in ground and well water is increasing (Manassaram et al, 2006;Burow et al, 2010;Cockburn et al, 2010;Ward et al, 2010). The use of high levels of nitrate on rabbit performance was investigated by Gilman et al (1998); Bassuny et al (2004); Shehata (2005); and Djekoun-Bensoltane et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate is a serious problem worldwide, and recent research indicated that nitrate in ground and well water is increasing (Manassaram et al, 2006;Burow et al, 2010;Cockburn et al, 2010;Ward et al, 2010). The use of high levels of nitrate on rabbit performance was investigated by Gilman et al (1998); Bassuny et al (2004); Shehata (2005); and Djekoun-Bensoltane et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to nitrate or nitrite in drinking water is associated with methemoglobinemia in infants, and possibly cancer (Grosse et al, 2006) and selected reproductive and developmental outcomes (Manassaram et al, 2006). Levels in water can be measured accurately with laboratory assays, but in the context of a large epidemiologic study, this may be costprohibitive, and poses logistical challenges due to obtaining and transporting water samples.…”
Section: Introductionmentioning
confidence: 99%
“…There are some literatures which have demonstrated that methemoglobinemia can be associated with drinking of tube-well water. 6 As she is not having methemoglobin in normal range even after delivery, so it is also supporting that due to drinking contaminated water, her baseline value is on higher side. Though heterozygote's variety of methemoglobinemia can present as same pattern and for this genetic study is needed.…”
Section: Discussionmentioning
confidence: 77%
“…7 Our patient had excessive fatigability with mild tachypnea and tachycardia. As there are evidences which suggest that epidural anesthesia may further cause neonatal methemoglobinemia 6 and she was deeply cyanosed and fatigued so obstetricians have decided to go for elective caesarean section at 37th completed gestational weeks. In our case, the baby was affected due to the effect of general anesthesia but not due to methemoglobinemia.…”
Section: Discussionmentioning
confidence: 99%